Students’ adoption of Facebook in higher education: A gender-based comparison - Lee, Cheng Ean Catherine *; Chong, Alison Yu Wei (2016)
This paper aims to examine the gender differences of undergraduate students’ educational use of Facebook. The objectives of the study include identifying male and female students’ Facebook usage and assessing their perception on the usefulness and ease of use of Facebook in higher education. Using a quantitative research method, results reveal that male students have a higher frequency of Facebook visit (93.9%). Male students are more competent (48.5%) and more satisfied (42.2%) in using Facebook in comparison to female students. Although there were marginal differences between males’ and females’ perception for both usefulness and ease of use of Facebook (with mean differences ranging from 0.01 to 0.33); the differences in their overall perception on the usefulness and ease of use of Facebook were not significant (p<.05). In conclusion, male students had a higher overall score on the perceived usefulness of Facebook in higher education, while female students had a higher overall score on the perceived ease of use of Facebook.